Comparison of aerial surveys and pellet-based distance sampling methods for estimating deer density - Urbanek, Rachael E.; Nielsen, Clayton K.; Preuss, Timothy S.; Glowacki, Gary A. (Wildlife Society bulletin, 2012)
Wildlife biologists require density estimates for white-tailed deer (Odocoileus virginianus) to facilitate management. Aerial surveys are often used to obtain density estimates, but are subject to problems necessitating the consideration of novel techniques. During winters 2008 and 2009, we estimated deer density on 6 forest preserves near Chicago, Illinois, USA, using aerial surveys and pellet-based distance sampling (PBDS) methods to provide a comparison of these 2 density-estimation techniques. Density estimates from aerial surveys were obtained by dividing both the raw count of deer observed on each preserve (unadjusted aerial density) and the raw count divided by 0.75 (i.e., assuming a 75% detection rate; adjusted aerial density) by the area of the preserve. We calculated deer densities from PBDS methods using Program DISTANCE 5.0 (PBDS density) and used pairedt-tests to compare density estimates between PBDS and aerial survey techniques. Unadjusted aerial density (10–29 deer/km2) and adjusted aerial density (13–39 deer/km2) estimates did not differ (t 11= −1.99–0.44,P= 0.071–0.666) from PBDS density estimates (12–36 deer/km2). We also compared costs and found PBDS (US$85/survey) was 88% cheaper than aerial surveys (US$722/survey). Problems with bias and precision exist with both methods, and managers should give them serious consideration when choosing which method to use to estimate deer densities. Given accurate pellet decay and deposition rates and a large sample size of pellet groups, PBDS may be advantageous due to less bias in density estimates, no dependence on continuous snow cover, cheaper survey costs, and no need for elaborate equipment or for professional biologists to conduct surveys. However, future research needs to address how to reduce coefficient of variations and confidence intervals for PBDS so that differences among years can be better differentiated.